Analisis Pendekatan Berdiferensiasi pada Hasil Belajar Geografi Kurikulum Merdeka pada Materi Keanekaragaman Hayati Kelas XI SMA Negeri 4 Medan - Sartika Permata Sari; Sugiharto (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study aims to analyze the effect of implementing a differentiated learning approach on geography learning outcomes in the biodiversity material for Grade XI students of SMA Negeri 4 Medan. The differentiated approach was applied to align the learning process with students’ needs, interests, and learning styles. This research employed a quasi-experimental method using a pretest-posttest control group design. The sample consisted of two classes, namely an experimental class using differentiated learning and a control class using conventional methods. Data were collected through observation, tests, documentation, and interviews, and analyzed using normality, homogeneity, and t-tests. The results showed a significant difference between the learning outcomes of the experimental and control classes. The average posttest score of the experimental class was higher than that of the control class, indicating that the differentiated learning approach positively influenced students’ geography learning outcomes.